Applying Participatory Processes to Address Conflicts Over the Conservation of Large Carnivores: Understanding Conditions for Successful Management - Salvatori, Valeria; Balian, Estelle; Blanco, Juan Carlos; Ciucci, Paolo; Demeter, László; Hartel, Tibor; Marsden, Katrina; Redpath, Stephen Mark; von Korff, Yorck; Young, Juliette Claire (Frontiers in Ecology and Evolution, 2020)
Social conflicts over large carnivores are becoming more frequent following the general recovery of large carnivores in human shaped landscapes in Europe. To manage conflicts over large carnivores a detailed knowledge is necessary on the social, economic, cultural but also interpersonal dimensions of the conflicts. This can be achieved through a participatory engagement of all stakeholders within a procedure tailored to local contexts. We looked at conditions necessary for implementing the above approach in areas of intense large carnivores-human conflict across Europe (bear and wolves), and where traditional management conflict policies do not appear to be successful, as often based on urgent responses to emergency situations. We focussed on four areas in Europe where we interviewed stakeholders to characterize the conflicts and assess the potential for mitigation interventions through participatory processes. We focused on four key aspects related to social conflicts: (a) perception of the current situation and relationship with other stakeholders; (b) availability and accessibility of information and communication; (c) economic, ecological and social impacts; and (d) promotion of coexistence and participatory processes. Interviews were analyzed following the Redpath et al (2013) framework. We show that (lack of) trust between stakeholders and the relevant authorities as well as the lack of genuine communication among stakeholders are the key features that characterize social conflicts related to large carnivores With specific reference to large carnivores, the lack or inaccessibility of reliable information is reported in all cases by all stakeholders, as well as the need for proactive and inclusive policies developed and implemented by the relevant authorities. A consistent message was that support and engagement from relevant management institutions is pivotal for effective management of conflicts over large carnivores. Our findings highlight the importance for conflict mitigation of a deeper and mutual understanding of issues to be addressed through participatory processes.